TRANSLATION TECHNIQUE APPLIED IN TRANSLATING NOVEL ENTITLED THE RED PYRAMID (ENGLISH-INDONESIAN TRANSLATION) - Ni Made Arnita Yanti (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
The aims of the study are to classify and describe the literal translation and idiomatic translation. The theory used in this research is translation theory proposed by Larson. The words or phrases are obtained from the novel entitled The Red Pyramid by Rick Riordan. The result of this study are all kinds of translation such as literal and idiomatic translation and those seven procedures of translation such as borrowing, calque, literal translation, transposition, modulation, equivalence and adaptation could be applied in order to translate the source language into target language.